2021
DOI: 10.1039/d1sc04094d
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the N-coordinated single-atom Ni sites in heterogeneous electrocatalysts for CO2 reduction reaction

Abstract: Heterogeneous Ni−N−C single-atom catalysts (SACs) have attracted great research interest regarding their capability in facilitating the CO2 reduction reaction (CO2RR), with CO accounting for the major product. However, the fundamental...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…[ 54 ] The free energy change for COOH* formation on NiN 4 –Ni sites (0.66 eV) was slightly lower than that of NiN 4 –N sites (0.69 eV), suggesting that Ni atoms act as active sites for CO 2 RR (Figure 4d; Table S4, Supporting Information). [ 54 ] It is worth noting that the free energy change for COOH* formation on Ni and N sites is consistent with recent theoretical estimates on pyrrolic N‐coordinated NiN 4 sites, [ 58 ] and is lower than the absorption free energy of COOH* formation on pyridinic N–coordinated NiN 4 sites (>1.6 V). [ 11,15,55,59 ] Although NiN 4 Ni exhibits a slightly stronger binding strength of COOH* than that of NiN 4 N, the free energy path of CO* desorption from the surface of NiN 4 –N (0.38 eV) were thermodynamically more favorable than that on NiN 4 Ni (0.07 eV), suggesting that pyrrolic N favored the CO desorption from the NiN 4 sites.…”
Section: Resultssupporting
confidence: 86%
“…[ 54 ] The free energy change for COOH* formation on NiN 4 –Ni sites (0.66 eV) was slightly lower than that of NiN 4 –N sites (0.69 eV), suggesting that Ni atoms act as active sites for CO 2 RR (Figure 4d; Table S4, Supporting Information). [ 54 ] It is worth noting that the free energy change for COOH* formation on Ni and N sites is consistent with recent theoretical estimates on pyrrolic N‐coordinated NiN 4 sites, [ 58 ] and is lower than the absorption free energy of COOH* formation on pyridinic N–coordinated NiN 4 sites (>1.6 V). [ 11,15,55,59 ] Although NiN 4 Ni exhibits a slightly stronger binding strength of COOH* than that of NiN 4 N, the free energy path of CO* desorption from the surface of NiN 4 –N (0.38 eV) were thermodynamically more favorable than that on NiN 4 Ni (0.07 eV), suggesting that pyrrolic N favored the CO desorption from the NiN 4 sites.…”
Section: Resultssupporting
confidence: 86%
“…Indeed, it has been demonstrated that formation of the chemisorbed CO 2 molecule (*CO 2 ) plays a vital role in the CO 2 RR for numerous catalysts. [32][33][34][35] Nevertheless, physisorbed CO 2 may also contribute to the CO 2 RR. For example, the onestep reduction process in which physisorbed CO 2 reacts with surface-bound *H has been established as the key pathway for formate production.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, on the M–N–C catalysts, *COOH can also exhibit the trans -COOH (H-down) adsorption configuration in addition to the cis -COOH (H-up) configuration. 42,43 Thus, we examine the adsorption configurations and adsorption energies of trans -COOH (H-down) on Ni/Fe–N 6 –Gra and Fe/Zn–N 6 –Gra. The calculation results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%